Musculoskeletal disorders in office employees: outpatient treatment options - Elena S. Akarachkova; Olga V. Kotova (LLC "MEDIAFORMAT", 2024)
Musculoskeletal neck, shoulder, upper extremity, low back pain is a disorder that is most common in office employees. Furthermore, neck pain and low back pain are the most prevalent. Neck pain and low back pain are in Top-5 of the disorders contributing to disability, ahead of other disorders, such as diabetes mellitus, chronic lung diseases, coronary artery disease. The paper considers pathogenetic features of musculoskeletal disorders developing in office employees, along with treatment options with emphasis on the neurotropic vitamins and their combinations with NSAIDs.